Pedunculate cirripedes of the genus Pollicipes: 25 years after Margaret Barnes' review - Cruz, T (2022)
Twenty-five years ago, Margaret Barnes reviewed the genus Pollicipes published in Oceanography and Marine Biology: An Annual Review. Our review complements and updates Barnes (1996). An endemic species of Pollicipes, P. caboverdensis, from Cape Verde Islands, has since been described, joining the three previously known extant species (P. polymerus, northeastern Pacific Ocean, P. elegans, tropical eastern Pacific Ocean, and P. pollicipes, north-eastern Atlantic Ocean). Most research has been on Pollicipes polymerus and P. pollicipes. We provide a georeferenced map of the worldwide distribution of Pollicipes. All Pollicipes species are harvested throughout their geographic distributions with varying intensity and levels of management. Phylogeography and population genetics are new areas developed since Barnes (1996). We update systematics and morphological studies (adult descriptions, cirral form and function, and adhesion). Various aspects of the life history of Pollicipes (reproduction, larval phase, settlement, recruitment and growth), the biological assemblages associated with Pollicipes and post-settlement population processes are reviewed. Pollution and geochemical studies are outlined before a detailed appraisal of Atlantic and Pacific fisheries. Considerable progress has been made in emerging areas, particularly phylogeography, adhesion and cement, fisheries management and aquaculture. Research gaps are highlighted, despite the much progress in the last quarter-century.